Effects of storage time on chilled sperm characteristics of three exotic boars reared under Cameroonian production conditions - Fonou Tadiesse Lavoisier; Vemo Bertin Narcisse; Guiekep Nounamo Jemima; Niakam Tchouankap Suzanne Esther; Chongsi Margarette; Kenfack Augustave; Boufack Judith Laure (Universitas Airlangga, 2026)
The semen quality of exotic boar breeds introduced into Cameroon has been poorly assessed, and the characteristics of their chilled spermatozoa remain largely unknown. In artificial insemination (AI) programs, regular monitoring of semen quality is essential to maintain high reproductive performance. This study aimed to evaluate the response of semen from Landrace, Large White, and Duroc boars to chilled storage. Adult boars weighing 145-194.3 kg were housed individually in standard finishing pens (12.96 m²) equipped with a feeder and drinker. Semen was collected, chilled, and evaluated at 0, 24, 48, and 72 hours after collection. Analysis of fresh semen showed that sperm concentration was significantly higher (p < 0.05) in Duroc (218.6 ± 18.54 × 10⁶spz/mL) and Large White (200.6 ± 19.07 × 10⁶spz/mL) than in Landrace (149.2 ± 26.5 × 10⁶spz/mL), whereas semen volume showed the opposite trend. After 72 hours of storage, only Duroc semen exhibited significant reductions (p < 0.05) in the percentage of normal sperm cells (NSC), sperm viability, sperm membrane integrity, and seminal pH. In contrast, sperm kinematic parameters (TM, PM, VAP, VSL, VCL, and LIN) declined significantly (p < 0.05) with storage time in Landrace and Large White semen. In conclusion, semen from Landrace and Large White boars showed greater tolerance to chilled storage than semen from Duroc boars.